Deformation and fracture of a thick-walled pipeline made of nonlinearly elastic material - Mavzovin Vladimir; Karakhanyan Vadim; Ovchinnikov Igor (E3S Web of Conferences, 2024)
The problem of calculating the stress-strain state of a thick-walled pipeline subjected to the joint action of force load, temperature and corrosion wear is considered. The influence of temperature on the mechanical properties of the pipeline material, as well as on the rate of corrosion wear are taken into account. Such relations of material deformation model and corrosion wear model are used, which allowed to obtain an analytical solution. The analytical solution will allow to perform a timely and correct analysis of the stress state of a thick-walled pipeline, to determine the value of the ultimate pressure for a given pipe wall thickness, to determine the ultimate service life of the pipeline at known initial parameters, limit condition and corrosion wear regularities